Теоретичні й практичні аспекти економіки, права та психології сучасності - Львівський інститут ПрАТ «ВНЗ «МАУП» (My University, 2025)
У збірнику представлено матеріали мультидисциплінарної науково-практичної конференції здобувачів вищої освіти, що відбулась 15 травня 2025 р. у Львівському інституті ПрАТ «ВНЗ «МАУП». Видання призначене для широкого кола здобувачів вищої освіти, аспірантів, молодих вчених та практиків. The collection presents the materials of the multidisciplinary scientific and practical conference of higher education students, which took place on May 15, 2025 at the Lviv Institute of PJSC "VNI "MAUP". The publication is intended for a wide range of higher education students, postgraduate students, young scientists and practitioners.